Análisis de la difusión de la agenda cultural de la CCE Núcleo de Chimborazo y su impacto en la imagen institucional, enero-junio 2018 - Unach (2019)
In this research entitled “Analysis of the Diffusion of the Cultural Agenda of the CEC Núcleo de Chimborazo and its Impact on the Institutional Image, January-June 2018” ; the objective was to carry out an analysis of the cultural agenda handled by the CCE Núcleo of Chimborazo and the impact that this generates in the citizenship, the creation and management that is given to the information that the institution has as well as the different forms of dissemination of the multiple cultural artistic activities and events that are carried out continuously in the city, through all of this to know how you create an impact to the institutional image. Being a field research and descriptive work, by means of information collection instruments that were applied in this research, data could be obtained that little by little were generating ideas based on new communication strategies that is the proposal of this work, the tools used were surveys applied to the urban sector of Riobamba, in the analysis of the results a lack of organized work was identified in the communication department of the institution, giving more importance to the dissemination of contents; also interviews where it was also known how fundamental is a correct design management, color, graphics in the cultural agenda as in personal invitations for certain activities, among others. The theoretical foundation that is applied through the analysis of books, articles, the website of the institution, as well as their social networks and traditional media.